CTA Annual Report 2007 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2008)
The CTA reports on its activities during 2007 through themes such as agriculture, environment, agricultural trade, information and communication management, organizational capacity development, and other cross-cutting issues.